2021
DOI: 10.1089/neu.2021.0280
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Discomplete Spinal Lesions: New Evidence from Pain-Autonomic Interaction in Spinal Cord Injury

Abstract: The clinical evaluation of spinal afferents is an important diagnostic and prognostic marker for neurological and functional recovery after spinal cord injury (SCI). Particularly important regarding neuropathic pain following SCI is the function of the spinothalamic tract (STT) conveying nociceptive and temperature information. Here, we investigated the added value of neurophysiological methods revealing discomplete STT lesions, i.e., residual axonal sparing in clinically complete STT lesions. Specifically, cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Standardized sensory examination according to International Standards for Neurological Classification of SCI (ISNCSCI) in subacute traumatic and ischemic SCI patients observed within the European Multicenter Study about Spinal Cord Injury (EMSCI) revealed relative preservation of the spinothalamic tract (pinprick sensation), which predisposes for NP presentation (unpublished observation). In clinically sensorimotor complete SCI subjects (AIS-A), an instrumented analysis with contact-heat evoked measurements (CHEPS) also identified partial preservation of the spinothalamic tract to be associated with NP (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Standardized sensory examination according to International Standards for Neurological Classification of SCI (ISNCSCI) in subacute traumatic and ischemic SCI patients observed within the European Multicenter Study about Spinal Cord Injury (EMSCI) revealed relative preservation of the spinothalamic tract (pinprick sensation), which predisposes for NP presentation (unpublished observation). In clinically sensorimotor complete SCI subjects (AIS-A), an instrumented analysis with contact-heat evoked measurements (CHEPS) also identified partial preservation of the spinothalamic tract to be associated with NP (35).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the poor health condition of SNS iDTR mice in our hands with the presentation of seizures was not sufficient to inflict contusion SCI and a prolonged survival period on these animals. In SNS tdTomato we observed a leaky reporter expression that based on breeding records could be traced back to Rosa26LSL-tdTomato mice -A), an instrumented analysis with contact-heat evoked measurements (CHEPS) also identified partial preservation of the spinothalamic tract to be associated with NP (35).…”
Section: Nociceptor Hypersensitivity Is Observed In Sci Subjects Up T...mentioning
confidence: 95%
See 1 more Smart Citation
“…This might be an explanation for the observed differences in habituation for the three different readouts. In this regard, a recent study from our group (Lütolf et al, 2021) also reported diverging results when investigating the integrity of ascending nociceptive projections in subjects with spinal cord injury employing the same three readouts. There a potential contribution of different neural structures in the generation of pain ratings, CHEPs and SSRs were discussed to explain the diverging results.…”
Section: Differences In Pain Habituation and Neural Substratesmentioning
confidence: 97%
“…In contrast with other autonomic signals, the SSR is thought to be largely independent of adrenergic agents, haemodynamic variability and respiratory rate [41]. While SSR has shown its ability to respond to noxious stimuli such as laser or thermode pulses [6,26,28] and to detect hypalgesia due to neural lesions such as syringomyelia [48], its ability to detect abnormal subjective perception, including pain, in states of pathological or experimental hypersensitivity consistent with routine clinical practice has scarcely been explored [31,39].…”
Section: Introductionmentioning
confidence: 99%